2018
DOI: 10.5781/jwj.2018.36.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Spatter Generation During Constant Voltage DC-AC Pulse Tandem Gas Metal Arc Welding Process

Abstract: To enhance productivity and provide high quality production material in a GMA welding process, weld quality, productivity and cost reduction affects the number of process variables. In addition, a reliable welding process and conditions must be implemented to reduce weld structure failure. In various industries the welding process mathematical model is not fully formulated for the process parameter and on the welding conditions, therefore only partial variables can be predicted. The research investigates the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In AC-GMAW, optimisation of the pulse waveform is complicated because the number of control parameters is twice that of GMAW-P [22]; recently, fully digital controlled power sources with built-in parameter sets have been developed for AC-GMAW, and a reliable droplet transfer and arc length control have been reported [23, 24]. Stable drop transfer and arc formation have been confirmed for an asynchronous T-GMAW process with AC-GMAW introduced into the trailing process [25]. In GMAW-P, the peak current is higher than that in standard GMAW, and a stiffer arc is established.…”
Section: Introductionmentioning
confidence: 99%
“…In AC-GMAW, optimisation of the pulse waveform is complicated because the number of control parameters is twice that of GMAW-P [22]; recently, fully digital controlled power sources with built-in parameter sets have been developed for AC-GMAW, and a reliable droplet transfer and arc length control have been reported [23, 24]. Stable drop transfer and arc formation have been confirmed for an asynchronous T-GMAW process with AC-GMAW introduced into the trailing process [25]. In GMAW-P, the peak current is higher than that in standard GMAW, and a stiffer arc is established.…”
Section: Introductionmentioning
confidence: 99%
“…Spatter is one common welding defect that is generated during GMAW. In a recent work, Kang et al showed spatter can be minimized by utilizing proper inter-wire distance and range of current for leading and lagging electrode 5) . Flux cored arc welding is a special type gas metal arc welding process in which annular consumable electrode is filled by flux.…”
Section: Introductionmentioning
confidence: 99%